55 heroes in Antwerpen - Michiels, Freddy, 1942- (Antwerpen : Artus Uitgevers, 2015)
In this book we will introduce you to 55 heroes from the recent or more distant past of Antwerp: 55 statues, varying greatly in shape, ambition and their impact on the architecture of Antwerp. All these heroes touched our hearts and we therefore feel that they deserve a place in our midst. A commemorative place, a fixed meeting point that can serve as inspiration or reminder. 55 heroes who deserve a monument.
Text in English, French and Dutch.
Keywords: Heroes -- Belgium -- Antwerp; Antwerp (Belgium) -- History